Planar Waves of the Buffered Bistable System - Xiaohuan Wang; Guangying Lv (Abstract and Applied Analysis)
This paper is concerned with the large time behavior of disturbed planar fronts in the buffered bistable system in ℝn (n≥2). We first show that the large time behavior of the disturbed fronts can be approximated by that of the mean curvature flow with a drift term for all large time up to t=+∞. And then we prove that the planar front is asymptotically stable in L∞(ℝn) under ergodic perturbations, which include quasiperiodic and almost periodic ones as special cases.